Two wheels south : a motorcycle adventure from Brooklyn to Ushuaia - Corea, Matias, ....- (Berlin : Gestalten, 2019)
Come along for the adventure of a lifetime: revel in the freedom of a road trip, and join two friends riding into the unknown—traveling 20,000 miles south on their trusty BMW air-cooled G/S overland haulers. From the Guatemalan jungle, to the magical, desolate Bolivian salt flats, the high roads of the Peruvian Andes, all the way to Ushuaia, the Land of Fire. Matias Corea shares his insights on how to prepare, choose the right motorcycle, what to pack, how to plan the route, where to camp and last but not least: How to prepare your mind. Setbacks and breaking down are part of the adventure, but preparation and being on the road teach you the confidence to tackle any problem. Follow Matias Corea and his friend Joel through the American South, Central America over the Darien Gap and beyond, over wooden cracking jungle bridges in Colombia and to dry lake high plateaus in Argentina.
Keywords: Reizen